(untitled) (Journal of Engineering, 2022)
Car drivers hear many kinds of noise inside their vehicles’ cabins, and the most annoying ones are the noise generated by tires, engines, and outside winds. Noise affects the comfort of the passengers inside the cabin, and it’s sad to say that modern cars are noisier in many kinds of noise signals due to using a lot of plastic materials in new budget cars. For expensive and luxury cars, the problem is solved by using better sound insulation materials, but for the budget ones, the approach used here is effective. It is called Active Noise Cancellation and can be done using analog or digital electronics. An operational amplifier and filters are used for the analog one, and in the digital one, signal processor chips are used. In engineering, cost reduction is a significant goal, and it is here, by using low-cost signal processor chips to achieve this, and our nominee is the Arduino processor. It is a low-cost open-source processor used in many digital control fields but not for noise cancellation, which is the concern of this paper. Considering the moderate signal processing capabilities of Arduino processors, a decision is required on what type of cabin noise signals our nominee can remove, and our selection is road noise. To a great extent, road noise relates to its quality, and the metric of concern is road roughness. In this work, three types of roughness are considered, low, medium, and high, the noise obtained from each type is analyzed, and countermeasures were applied to reduce them. Max cancellation obtained per three types, low, medium, and high roughness are 10 to 12 dB.